Evaluation of isolation between two differential microstrip antennas - Liu, Huanli (Nanyang Technological University, 2021)
This report gives the design of two differential microstrip patch antennas on the same substrate. First, background information on the antenna and the microstrip patch antenna is presented. Second, the design equation of single-ended microstrip patch antenna is used to determine the length of differential microstrip rectangular patch. Third, the width and feed point of the differential microstrip rectangular patch are determined and designed using SONNET. The isolation results between the two differential microstrip patch antennas are related to the S-parameters of the differential pattern, which can be obtained from MATLAB. In addition, two differential circular patch antennas are designed and compared with two differential rectangular patch antennas. The results show that the insertion loss of the circular antennas is -14 dB, while that of the rectangular antennasis -12.2 dB, which means that the two differential circular antennas have better isolation.